1987
DOI: 10.1099/00221287-133-4-935
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glucosyltransferase Expressed from a Streptococcus Sobrinus Gene Cloned in Escherichia Coli

Abstract: The gene encoding a glucosyltransferase which synthesized water-insoluble glucan, g t f l , previously cloned from Streptococcus sobrinus strain MFe28 (mutans serotype h) into a bacteriophage 2 vector, was subcloned into the plasmid pBR322. The recombinant plasmid was stable in Escherichia coli and gtjlr was efficiently expressed. The GTF-I expressed in E. coli was compared to the corresponding enzymes in S. sobrinus strains MFe28 (serotype h), B13 (serotype d ) and 6715.(serotype g ) and shown to resemble the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…Even in the C-terminal region there is a highly homologous region (94%) between residues 1181 and 1320, which is shown to be essential for glucan binding in ISG synthesis (see above). These two proteins are indeed indistinguishable in antigenicity (27). By contrast, either of these proteins shows a rather low homology with proteins of gtJB and gtfC from S. mutans GS-5 (-60%).…”
Section: Restriction Mapmentioning
confidence: 92%
See 2 more Smart Citations
“…Even in the C-terminal region there is a highly homologous region (94%) between residues 1181 and 1320, which is shown to be essential for glucan binding in ISG synthesis (see above). These two proteins are indeed indistinguishable in antigenicity (27). By contrast, either of these proteins shows a rather low homology with proteins of gtJB and gtfC from S. mutans GS-5 (-60%).…”
Section: Restriction Mapmentioning
confidence: 92%
“…Glucan-binding fragments were isolated by tryptic digestion of GTF proteins from S. sobrinus, but none of them showed glucan-synthesizing activity (18,22). Of several molecular cloning studies of GTF genes from mutans streptococci (1,7,10,13,14,25,27,29,31), Ferretti et al (7) * Corresponding author.were the first to determine the complete nucleotide sequence of the GTF-I gene from a strain of S. sobrinus (MFe28); they have located a glucan-binding site in a carboxy-terminal region of the GTF-I protein, which is essential for the enzyme activity. However, it is not yet known what roles the regions near the N terminus play or how they are correlated with the roles of C-terminal regions in GTF-I activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that a 3.3-kilobase fragment of chromosomal DNA of MFe2ST reveals differences between MFe28T and S. sobrinus strains in Southern blotting hybridization experiments (21). Despite the relatively high degree of DNA homology observed between the monkey plaque strains and strains of S. sobrinus, compared with representatives of the other species within the mutans streptococci, the results show that the monkey strains and S. sobrinus are sufficiently dissimilar to warrant separate species status, for which we propose the name Streptococcus downei.…”
Section: Resultsmentioning
confidence: 99%
“…Genes responsible for glucan synthesis in S. mutans are gtfB (Shiroza et al, 1987), which synthesizes an ␣-1,3-linked insoluble glucan, gtfC (Pucci et al, 1987), which synthesizes glucan with both ␣-1,3 and ␣-1,6 linkages, and gtfD (Honda et al, 1990), which synthesizes a soluble ␣-1,6-linked glucan. Similarly, the products of gtfI (Russell et al, 1987) and gtfS (Gilmore et al, 1990) genes of S. sobrinus synthesize insoluble and soluble glucan products, respectively. Mutational inactivation techniques have shown that each of these gene products is important to the cariogenicity of the respective mutans streptococcal strain.…”
Section: (B) Glucosyltransferases (Gtfs)mentioning
confidence: 99%